ENDODONTIC APPLICATIONS OF 3D PRINTING (Academia Journal of Medicine, 2025)
Current research suggests an emerging value of 3D printed guides use in the  endodontic field. Computer-aided design and manufacturing technologies can be  used to create 3D printed guides with endodontic clinical applications. Computer aided design (CAD) and computer-aided manufacturing (CAM) technologies can  leverage cone beam computed tomography data for production of objects used in  surgical and nonsurgical endodontics and in educational settings. The aim of this  article was to review all current applications of 3D printing in endodontics and to  speculate upon future directions for research and clinical use within the specialty.  Documented solutions to endodontic challenges include: guided access with pulp  canal obliteration, applications in auto transplantation, pre-surgical planning  and educational modelling and accurate location of osteotomy perforation sites.  Future research directions should include clinical outcomes assessments of  treatments employing 3D printed objects.
Keywords: Endodontics; 3D printing; Guided endodontics